Métodos Iterativos para Sistemas Lineales Grandes - Figueroa-Mata, Geovanni; Carrera-Retana, Ernesto (Instituto Tecnológico de Costa Rica, 2012)
The computing power built into the graphics processing units (GPU) from Nvidia new video cards has permitted parallel processing to solve problems that require computational power and are not linked to the graphical environment for that were originally created. This project apply this technology to the solution of large linear systems.
Proyecto de Investigación (Código 5402-1701-0101) Instituto Tecnológico de Costa Rica. Vicerrectoría de Investigación y Extensión (VIE). Escuela de Matemática, 2012
Keywords: Matrices; Procesamiento; Gradiente; Características